Evaluation of deflection forces of orthodontic wires with different ligation types - José Fernando Castanha HENRIQUES; Rodrigo Hitoshi HIGA; Nayara Thiago SEMENARA; Guilherme JANSON; Thais Maria Freire FERNANDES; Renata SATHLER (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study was to evaluate deflection forces of orthodontic wires of different alloys engaged into conventional brackets using several ligation types. Stainless steel, conventional superelastic nickel-titanium and thermally activated nickel-titanium archwires tied into conventional brackets by a ring-shaped elastomeric ligature (RSEL), a 8-shaped elastomeric ligature (8SEL) and a metal ligature (ML) were tested. A clinical simulation device was created especially for this study and forces were measured with an Instron Universal Testing Machine. For the testing procedure, the block representing the maxillary right central incisor was moved 0.5 and 1 mm bucco-lingually at a constant speed of 2 mm/min, and the forces released by the wires were recorded, in accordance with the ISO 15841 guidelines. In general, the RSEL showed lighter forces, while 8SEL and ML showed higher values. At the 0.5 mm deflection, the 8SEL presented the greatest force, but at the 1.0 mm deflection the ML had a statistically similar force. Based on our evaluations, to obtain lighter forces, the thermally activated nickel-titanium wire with the RSEL are recommended, while the steel wire with the 8SEL or the ML are recommended when larger forces are desired. The ML exhibited the highest force increase with increased deflections, compared with the elastomeric ligatures.